2017
DOI: 10.1155/2017/6057609
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase 2 Regulates NLRP3 Inflammasome Activation in the Brain after Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is a leading cause of death and disability worldwide. After the initial primary mechanical injury, a complex secondary injury cascade involving oxidative stress and neuroinflammation follows, which may exacerbate the injury and complicate the healing process. NADPH oxidase 2 (NOX2) is a major contributor to oxidative stress in TBI pathology, and inhibition of NOX2 is neuroprotective. The NLRP3 inflammasome can become activated in response to oxidative stress, but little is known ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 62 publications
2
67
0
Order By: Relevance
“…In addition, a number of recent studies have found that pharmacological treatments that directly or indirectly target this inflammasome can reduce its activity following moderate-to-severe TBI. These treatments are broadly broken into four groups: (i) treatments derived from naturally occurring compounds (e.g., mangiferin [83], omega-3 fatty acids [71], and apocynin [84]); (ii) repurposed medications (e.g., propofol [85], and telmisartan [86]); (iii) inhibitors of NLRP3-associated molecules (e.g., ASC antibodies [87], NF-κB inhibitor, Bay 11-7082 [88][89][90][91]); and (iv) specific NLRP3 inflammasome inhibitors (e.g., MCC950 [69], JC-124 [92]). While the first three treatment categories have been shown to decrease NLRP3 inflammasome activity as well as demonstrating a neuroprotective effect, they do not target NLRP3 activation specifically.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of recent studies have found that pharmacological treatments that directly or indirectly target this inflammasome can reduce its activity following moderate-to-severe TBI. These treatments are broadly broken into four groups: (i) treatments derived from naturally occurring compounds (e.g., mangiferin [83], omega-3 fatty acids [71], and apocynin [84]); (ii) repurposed medications (e.g., propofol [85], and telmisartan [86]); (iii) inhibitors of NLRP3-associated molecules (e.g., ASC antibodies [87], NF-κB inhibitor, Bay 11-7082 [88][89][90][91]); and (iv) specific NLRP3 inflammasome inhibitors (e.g., MCC950 [69], JC-124 [92]). While the first three treatment categories have been shown to decrease NLRP3 inflammasome activity as well as demonstrating a neuroprotective effect, they do not target NLRP3 activation specifically.…”
Section: Nlrp3 As a Therapeutic Target For Tbimentioning
confidence: 99%
“…Given the increasing awareness that neuroinflammation can interact with other aspects of TBI pathophysiology, it is likely that alterations or manipulation of the NLRP3 inflammasome will have multiple pathophysiological consequences. For example, recent studies have found that a relationship exists between neuroinflammation, oxidative stress, and blood-brain barrier permeability after TBI [84,108,109]. The involvement of the NLRP3 inflammasome in these interactions is not yet known; however, MCC950 treatment TBI was found to reduce the extent of blood-brain barrier damage and apoptosis in the acute stages after in TBI mice [70].…”
Section: Effect Of Nlrp3 Inflammasome On Tbi Pathophysiologymentioning
confidence: 99%
“…In addition, resveratrol, a natural autophagy inducer, was demonstrated to function in the inhibition of the NLRP3 inflammasome in cerebral cortex through the promotion of sirtuin 1 (SIR1) signaling pathway ( Zou et al, 2018 ). Furthermore, NOX2 was shown to contribute to the progression of traumatic brain injury, and the administration of the NOX2 inhibitors led to the a neuroprotective effect through the suppression of the NLRP3 inflammasome ( Ma et al, 2017 ).…”
Section: Nlrp3 Inflammasome In Cns Disordersmentioning
confidence: 99%
“…In particular, bone resorption and differentiation of osteoclast precursors to mature cells is regulated by the pro-inflammatory transcription factors, NFB, and RANKL [40,41]. Of note, we reported increased chronic inflammatory activation, involving the mobilization of bone marrow derived immune cells, within both blood and brain following a TBI [25,[33][34][35][36]. Consistent with these findings, the key NFB genes, RelA/p65 and Birc3, were dysregulated in the bone marrow Taken together, our study raises the interesting possibility that TBI fosters a chronic proinflammatory state within the bone marrow niche, culminating in increased bone resorption.…”
Section: Discussionmentioning
confidence: 76%